PHYTOPLANKTON CHANGES IN SOME INLAND WATER HABITAT OF CENTRAL KALIMANTAN, INDONESIA - Sulastri, Sulastri; Hartoto, Dede Irving (BERITA BIOLOGI, 2000)
The changes in the density, number of genera, diversity index of phytoplankton in some oxbow lakes (LakeRengas, Lutan,Takapan) and lowland lake (Lake Sembuluh) are described.Phytoplankton samples collected in rainy season, dry season (1995 to 1997) and in the forest fire period (October 1997).Before forest fire period, most of the time the density of phytoplankton was high (489 to 759 individuals/1) in January or rainy season especially in oxbow lake system. The high number of phytoplankton in rainy season is not common in the standing water in the floodplain system. This is probably because of the type of water that is acid water with the pH (4.43 to 4.66) in Lake Rengas, Lake Lutan (4.93 to 5.93) and Lake Takapan (4.03 to 4.64).In acid water oxbow lake, only some certain species occurred in the dry season. In January (rainy season),the inputs of water from main river increase the pH and presumably also nutrient, as shown by higher conductivity.In Lake Rengas, the highest density found in June that dominated by one genera (Oocystis).These facts probably because of phytoplankton input from the river Rungan that also show high density of the same species.It is also showed that the number the number of genera is also high in rainy season. Nonetheless of index diversity changes is not clear. In October 1997, when the forest fire period the density of phytoplankton and some genera as a group of Euglenophyceae increased.The highest density was found in Lake Sembuluh that range from 10,507 to 39,536 individuals/1.The phytoplankton density of Lake Rengas, Lutan and Takapan are 3,254, 1,414 and 9,019 respectively.The relationship of forest fire to the phytoplankton density is briefly discussed.